Promoting Justice and Peace Through Islamic Education: Comparative Insights from Interfaith Engagements in Kenya and Indonesia - Alwy Ahmed Mohamed; Muhammad K. Ridwan (Walidem Institute and Publishing (WIP), 2025)
Objective: This study investigates the role of Islamic values in shaping interreligious relations within pluralistic societies, focusing on Kenya and Indonesia as comparative case studies. The objective is to analyse how Islamic teachings, particularly the principles of taʿāyush (coexistence), raḥma (compassion), and ʿadl (justice), inform Muslim engagement with non-Muslim communities in diverse socio-political contexts. Theoretical framework: The theoretical framework draws upon Qur’anic ethics and the Prophetic tradition as models for peaceful coexistence, contextualized within the broader discourse of religious pluralism and interfaith dialogue. Literature review: Prior studies on Islamic education and interfaith relations emphasize ethical principles like ʿadl, raḥma, and taʿāyush in conflict resolution. However, few compare regional approaches. This study fills that gap by analyzing Islamic peacebuilding practices across Kenya and Indonesia within the framework of the SDGs and religious pluralism. Method: Methodologically, this research employs a qualitative, comparative case study approach, integrating historical analysis, textual interpretation, and contemporary field data from both countries. Results: Findings reveal that Islamic traditions in both Kenya and Indonesia offer rich resources for fostering social cohesion and resisting sectarianism. Kenyan Muslim initiatives emphasize grassroots reconciliation in post-conflict zones, while Indonesian Islamic movements focus on institutional interfaith collaboration and education. These responses align with global peacebuilding frameworks, contributing to the realization of Sustainable Development Goal 16 (Peace, Justice, and Strong Institutions) and SDG 17 (Partnerships for the Goals). Implications: The study’s implications highlight the potential of Islamic interfaith engagement to mitigate religious tensions and promote inclusive governance. Novelty: Its novelty lies in the cross-regional comparison of Islamic interfaith strategies and its grounding in both classical Islamic sources and contemporary global development agendas. The research offers a nuanced, actionable model for faith-based peacebuilding in multicultural contexts.